Rare Langerhans cell histiocytosis in children: a case report - Fadil, Lina; Almajid, Emtenan (International Journal of Research in Medical Sciences, 2019)
Langerhans cell histiocytosis (LCH) is a rare disease, formally known as histiocytosis X that is characterized by abnormal proliferation of histiocytes derived from bone marrow (Langerhans cells), joined with leucocytes, eosinophils, neutrophils, lymphocytes, plasma cells and giant multi-nucleated cells causing tissue destruction. One of the first signs of LCH is oral manifestation, in some cases, the oral cavity may be the only affected area. With the chance of oral lesion incidence in LCH being 77%.Initial symptoms are generally nonspecific, which can easily cause misdiagnoses.The purpose of reporting this case is to discuss the features of LCH clinically and radiographically and in the role of the dentist when diagnosing such lesions for a proper management. An 11-year-old boy reported a complaint of swelling in the left side of the lower jaw that is asymptomatic and had been gradually increasing in size for the past 6 months without any improvements. After preforming a biopsy and diagnosing the lesion as LCH, the patient was then treated with a dose of vinblastine (6 mg/m2 intravenous bolus) for 24 weeks as a total period. Two years follow up; the patient showed no sign of recurrence and is in good general condition. In conclusion, reporting this case serves as documentation of the proper route of clinical assessment and diagnosis of LCH with the best possible treatment as guidance.